The Virtual Lock-in Amplifiers - Accuracy of Measurement Results in Light Transmission Experiments - Lintang Ratri Prastika; Lili Indarti; Hendro Hendro (Universitas Negeri Malang, 2021)
This research focuses on the analysis of the measurement result of the virtual lock-in amplifier (virtual-LIA) in the light transmission experiment as the trial step of developing the virtual-LIA. The virtual-LIA used in this research is designed by using the Vernier sensor DAQ as the data acquisition and the LabVIEW as the programming media. The design of virtual-LIA is based on the mathematical operations of LIA. The type of virtual-LIA is a single phase with the capabilities to process the external reference signal. Light transmission experiments are carried out using formazin polymer suspension with turbidity level of 3000 NTU, 3500 NTU, and 4000 NTU as the medium in which light is passed. The accuracy of the measurement results is known by comparing the results of virtual-LIA with real-LIA SR510. The experiments are also carried out in bright and darkroom conditions to determine the ability of virtual-LIA in reducing noise signals. Based on the experiment, the results obtained that the measurement accuracy of the virtual-LIA developed is above 94% compared to the LIA SR510. Virtual-LIA could measure small signals with and without noise with the average percentage of differences measured between dark and bright conditions is 0.54%.DOI: 10.17977/um024v6i12021p001